The geodetic, hull, and Steiner numbers of powers of paths - AbuGhneim, Omar A.,; Al-Khamaiseh, Basem,; Al-Ezeh, Hasan, (Utilitas Mathematica, 2014)
Let Pn+1 be the path of order n + 1 on the vertices v0,v1,...,vn and Pkn+1 is the power of Pn+1. In this paper, we find the geodetic, hull, and Steiner numbers of Pkn+1.